Podcasting for dummies - Morris, Tee; Tomasi, Chuck (--For dummies., 2020)
Expert info on producing podcasts. With more and more people turning to podcasts for on-demand, mobile entertainment and information, the market for new podcasts has never been healthier--or more competitive. Big companies and A-list celebrities are starting to get in on the action, so it's more important than ever to produce content that sets you apart. Podcasting For Dummies, 4th Edition offers a fast and easy way to get the know-how you need to produce and distribute your own podcast. Written by a pair of podcasting pioneers, this book shares insight on the technology behind recording, editing, and sharing podcasts along with tips on how to produce a pro-level podcast and find your audience. Inside: Getting the gear you need Finding your podcasting voice Preparing for interviews Recording your podcast Editing your podcast Promoting your podcast.